The Effectiveness of Mopila Media to Improve Students' Civic Skills in Pancasila Education Subject of Fourth Grade Elementary School - Vina Yunita Sari; Hamidaturrohmah; Naili Rofiqoh (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
The lack of implementation of interesting and interactive learning media in Pancasila education has an impact on the low civic skills of students. The research has been conducted to assess the effectiveness of Mopila (Monopoli Pancasila) media to improve the civic skills of fourth grade students in Pancasila Education. This research uses a quantitative research method by using a pre-experimental design of one-group pretest-posttest design which subject is students at SD Negeri 1 Bangsri. Data has been collected through questionnaire instruments, while the data is analyzed using normality test and paired sample t-test. The research results have demonstrated a significant increase between the pretest and posttest results of students' average scores from 49.1 with a percentage of 61% to 59.6 with a percentage of 74%. In addition, the significance value of p < 0.001 indicates that it is effective for improving students' civic skills, including intellectual skills and participation skills. The implementation of Mopila media is capable of creating an interactive, collaborative, and enjoyable the learning process, which allows students to think critically, participate actively, take responsibility in groups, participate in discussions, be confident in expressing opinions, and understand the values of Pancasila more satisfactory. Therefore, Mopila media is effective as an educational tool that improves the civic skills of students’ elementary school.